LESSON PLAN - Reski, Pilu (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2013)
A lesson plan is a teaches detailed description of the courseof instructionfor one class. A daily lesson plan is developed by a teacher to guide class instruction. Details will vary depending on the preference of the teacher, subject being covered, and the need and/or curiosity of students. there may be requirements mandated by the school system regarding the plan